The effect of ZnO on the sintering and stabilization of ZrO2 center dot MgO system - Nasar, R. S.; Cerqueira, M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 1999)
The sintering of ZrO2. MgO . ZnO powder has been investigated by TMA (Thermal Mechanical Analyser) and its phases analysed by XRD (X-ray diffraction pattern). The data obtained from sintering was studied by the Bannister equation and its dominant sintering mechanism was calculated. It was observed that the ZnO addition in the ZrO2. MgO solid solution lead to increased zirconia stabilization, According to the vacancies model, the ZnO addition did not lead to zirconia phases stabilization (PSZ). An analysis of the rate control in the initial stage of the sintering (region I) showed a mechanism of volume diffusion type. In other regions (regions II and III), the grain growth did lead to the Bannister equation deviation, which was observed by SEM (Scanning Electron Microscopy). These results were different from those demonstrated by other authors who studied the ZrO2. Y2O3 solid solution and obtained a mechanism of grain boundary diffusion type. (C) 1999 Published by Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: magnesia-PSZ; bannister equation; zirconia stabilization